Adherence to a Hypoglycemia Protocol in Hospitalized Patients: A Retrospective Analysis. Issue 1 (January 2021) - Tracy, Mary Fran; Manchester, Carol; Mathiason, Michelle A.; Wood, Jeff; Moore, Amy
Abstract : Background: Hypoglycemia can be a common occurrence in hospitalized patients, both those with and without diabetes. Hypoglycemia poses significant risks to hospitalized patients, including increased mortality. Objectives: This was a retrospective pre–post study of hypoglycemic patients in an academic medical center of an intervention to improve timely staff nurse adherence to a hypoglycemia protocol. The number of mild and severe hypoglycemia events pre- and postintervention, timeliness of adherence to the hypoglycemia protocol, the number of treatment interventions, and time to return patients to euglycemia were analyzed. Methods: Data from hospitalizations of patients who experienced hypoglycemia (<70 mg/dl) and met inclusion criteria 1 year prior to intervention and 3 years postintervention were extracted, including demographics, glycemic control medications, diagnostic-related group, length of stay, and Charlson comorbidity index. For clarity and to determine if any significant change was sustained, the analysis compared data from 1 year prior to intervention to the second-year postintervention. Results: A total of 7, 895 unique hypoglycemic events in 3, 819 patients experiencing 20, 094 hypoglycemic measures were included in the analysis. Patients were primarily adult, female, and White. Only 58.7% of the sample had diabetes; the median Charlson comorbidity index was 6. Results demonstrated improvement postintervention to registered nurse hypoglycemia protocol adherence regardless of age category or hypoglycemia severity. There was a significant reduction in median time from the first hypoglycemia measure to the second measure. In addition, there was a significant difference in the number of treatment interventions and reduction in time from the first hypoglycemia measure to return of patient to a blood glucose of ≥70 mg/dl. Discussion: These study results support that the use of a standardized hypoglycemia protocol and appropriate nurse workflows enables nurses to manage hypoglycemia promptly and effectively in most acute and critically ill hospitalized patients. Results also supported a differentiation in nurse workflow for patients with mild versus severe hypoglycemia. Implementing these interventions may result in avoidance or mitigation of the potential consequences of severe and/or sustained hypoglycemia.